Emergence and development of Joint Attention in infancy. - Escudero, Alfonso José; Carranza, José Antonio; Huescar, Elisa (Anales de Psicología / Annals of Psychology, 2013)
Joint Attention is the first step to build communication. Hence, its study is of great interest due to its influence on cognitive, social, emotional, and language development. This article presents a review of the research on the emergence and development of Joint Attention in infancy, highlighting the major points of discussion on this topic. We begin by examining the concept of intentionality in the definition of Joint Attention, followed by a description of the sequence of development of this capacity. We finish relating joint attention to language development and suggesting directions that can guide ulterior research in the field.